Disposal of wastewater containing Congo Red by synthesizing layer double hydroxide in-situ - 朱荣 崔康平 彭书传 杨远盛 陈天虎 安志环 徐晓春 (Chinese journal of geochemistry, 2006)
Based on the principle of synthesis, a new method was put forward to dispose Congo Red anion-containing dyestuff from wastewater and its feasibility was also examined. The principle of the method is described as follows： Mg^2＋ and Al^3＋ are hydrolyzed to form Mg/Al-LDH by adding Mg^2＋, Al^3＋ and NaOH in wastewater containing anion dyestuff, which is selectively intercalated with the interlayer of LDH in order to balance positive structural charge. While Mg^2＋ and Al^3＋ are co-precipitated to form LDH, the anion dyestuff in wastewater will be removed by LDH synthesized in-situ, as is confirmed by X-ray diffraction analysis of settlings and chemical analysis of aqueous samples. In this work, we studied the influence of Mg/Al mole ratio, pH value, time and temperature of reaction on the removal of anion dyestuff and the use of Mg and Al. The experimental results showed the maximum removal efficiency of anion dyestuff could be attained when pH value was 9.0, and Mg/Al mol ratio was 2 ： 1, reaction duration was 2 hours, and the effect of temperature was not remarkable, and the removal efficiency could reach 100%. Meanwhile, the Mg and Al added could be made good use of. This technology has the advantage of extraordinary efficiency of wastewater disposal.